Laboratory Study: Biopolymer from Extraction Seeds of Kluwih and Jackfruit for Enhanced Oil Recovery - Gajah, Ganesha; Arifin, Ihsan; Hidayat, Rahmad (Purnomo Yusgiantoro Center, 2019)
Polymer injection is a tertiary recovery that lowering the injection-oil water mobility ratio thus more efficient to produce oil. The increase in the polymer used for injection requires a large number of suitable polymers. Laboratory studies are necessary to develop new polymer produced domestically, with easily available materials, do not damage the environment, not harm the environment, and are economical. Seeds of Kluwih and Jackfruit contain the starch as a biopolymer for polymer injection because competent to act as a viscosifying agent thus repair the water-oil mobility ratio. Laboratory study is carried out through a series of processes. From starch extraction to polymer screening. The pure starch extraction is done by the wet method through a series of experiments carried out repeatedly. Observation with polymer screening was carried out on five tests. The rheology of polymers examined at two different polymer concentrations and temperatures to determine the viscosity at varying shear rate. Compatibility tests are reviewed to determine the homogeneous and the solubility of the polymer by the solvent. Filtration test is an entrapment test, know the relation between polymer molecule sizes and pore size distribution. The static polymer test is an adsorption test to know the polymer retention in the core caused by chemical interaction between core and polymer. The polymer flooding procedure is to know polymer performance to pushes remaining oil after waterflooding. The results show a pure starch without impurity content. In liquid, the starch acts as a viscosifying agent. Both of the two polymers degrade by shear rate and (polymer chain) broken at higher temperatures. Kluwih and Jackfruit starch dissolve homogeneously without a lumping. Polymer trapping and adsorption not dominantly occur by Jackfruit and Kluwih. The native polymer can enhance oil recovery but sensitive to the core and polymeric conditions.